Authentication of Art: assessing the performance of a machine learning based authentication method - Chen, Ailin (2020)
This paper compares the test results generated by applying the method for the authentication of paintings by Portuguese artist Amadeo de Souza Car-doso in the interest of exploring the generalisation properties of the algorithm on other artists or genres. This sets the base for the method to be improved and de-veloped accordingly in future applications for a broader audience in a wider set-ting. The obtained results show that the classifier obtained from the algorithm using paintings appears not to be directly applicable to drawings of the same art-ist. When the classifier is retrained for a different genre like Chinese paintings or artists like van Gogh, the algorithm appears to perform as well as the classifier on Amadeo paintings, i.e. the algorithm is sufficient for the classification of a specific type of artist or genre.